(untitled) (World Bulletin of Public Health, 2024)
Strabismus is not only a severe functional disease with the presence of gross cosmetic defects, but also, as a consequence, affects the patient’s psyche. Physical appearance is an important aspect of the socialization process. Another study found subnormal quality of life in parents of children with strabismus. There are reports that eliminating strabismus as a cosmetic flaw significantly improves patients’ self-esteem and socialization. Another study has shown that the removal of strabismus improves health-related quality of life in both children and their parents.